2005
DOI: 10.1017/s0269889705000700
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Epistemology of Suspicion: Psychoanalysis, Literature, and the Human Sciences

Abstract: ArgumentIn calling psychoanalysis a “school of suspicion” (Ricoeur 1970, 32), Ricoeur marks at once its use in a disposition characteristic of modernity: the disposition of suspicion. Modernity gives rise to various forms of suspicion, to modern forms of ressentiment and practices of disciplining oneself (the suspicion of oneself) as well as to an epistemology of suspicion. In this essay, I shall analyze the epistemological function of suspicion – which as the “paradigm of clues” (Ginzburg 1988) becomes the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…The third stage of analysis entailed a line‐by‐line examination of the text. Strowick () suggested that expressions used in speech may have hidden subtexts. These expressions may not directly constitute meaning, but they might indirectly indicate underlying issues.…”
Section: Methodsmentioning
confidence: 99%
“…The third stage of analysis entailed a line‐by‐line examination of the text. Strowick () suggested that expressions used in speech may have hidden subtexts. These expressions may not directly constitute meaning, but they might indirectly indicate underlying issues.…”
Section: Methodsmentioning
confidence: 99%
“…In the current climate of retrospection, however, as critics reflect on the intellectual legacy of recent decades and reassess methods of reading that have come to seem stale and unsurprising, the hermeneutics of suspicion is shifting from a mode of analysis to an object of analysis within literary studies. A style of interpretation that once seemed entirely selfevident and self-explanatory now finds itself squirming under the spotlight (Sedgwick 1997;Latour 2004;Strowick 2005;Best and Marcus 2009;Felski 2009;Love 2010). Why do so many scholars feel impelled to unmask and demystify the works that they read?…”
mentioning
confidence: 98%
“…In reality, suspicious reading has a larger, more variegated and more mundane history. As Elizabeth Strowick (2005) remarks, suspicion becomes a widely diffused interpretative method in the nineteenth century and early twentieth century, manifested in various forms of knowledge that are organized around the mistrust of surface appearance and the reading of clues, such as criminology, psychoanalysis, and literature. While Ricoeur's (1970: 33) account of the hermeneutics of suspicion stresses its heroic, oppositional, nay-saying qualities ("these three masters of suspicion are .…”
mentioning
confidence: 99%
“…The third stage of analysis entailed a line‐by‐line examination of the text. Strowick () explains that expressions used in texts and speech may have hidden subtexts. Such expressions themselves do not directly constitute meaning, but they can be indirect clues to underlying issues.…”
Section: Methodsmentioning
confidence: 99%